Rolprent, Televisie en die Omgewing - Pieter Jacobus Fourie (Communicare)
Against the background of the realist and expressionist film theories it is argued in this article that directors of films/videos on the environment should work in a more realistic style. The purpose should be to develop closer contact between the viewer and the environment. A brief descrip tion of realism and expressionism as two dominant styles in filmmaking and of Direct cinema and cinéma vérité is given, and the implications of these styles for the relationship Image/environment are discussed.